Short report: a rapid method for the differentiation of Burkholderia pseudomallei and Burkholderia thailandensis. - Wuthiekanun, V; Anuntagool, N; White, N; Sirisinha, S (2002)
A rapid method for the identification and differentiation of Burkholderia pseudomallei and Burkholderia thailandensis colonies is described. It consists of simultaneous use of 2 monoclonal antibody-based latex agglutination test systems. The anti-lipopolysaccharide test reacts with both species, whereas the anti-exopolysaccharide reacts only with B. pseudomallei. Compared with classical biochemical tests, the method is highly reproducible and accurate. It is particularly useful for the identification of the organisms in environmental specimens, which may contain both of these Burkholderia species.